(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
By the interaction between N-methylolthiourea and Co2+, Mn2+ acetates are obtained compounds that were later used for the synthesis of vinyl bifunctional groups containing polymerizable chelate complexes. These compounds are recommended to be used as crosslinkers for obtaining, on the basis of water-based soluble monomers, spatially cross-linked water-swellable copolymers with applied purpose. There are dynamics of water absorption of copolymers from the time of their stay in water.